Radiation Effects on Brain Extracellular Matrix - Grigorieva, Elvira V. (Frontiers in Oncology, 2020)
Radiotherapy is an important therapeutic approach to treating malignant tumors of different localization, including brain cancer. Glioblastoma multiforme (GBM) represents the most aggressive brain tumor, which develops relapsed disease during the first year after the surgical removal of the primary node, in spite of active adjuvant radiochemotherapy. More and more evidence suggests that the treatment’s success might be determined by the balance of expected antitumor effects of the treatment and its non-targeted side effects on the surrounding brain tissue. Radiation-induced damage of the GBM microenvironment might create tumor-susceptible niche facilitating proliferation and invasion of the residual glioma cells and the disease relapse. Understanding of molecular mechanisms of radiation-induced changes in brain ECM might help to reconsider and improve conventional anti-glioblastoma radiotherapy, taking into account the balance between its antitumor and ECM-destructing activities. Although little is currently known about the radiation-induced changes in brain ECM, this review summarizes current knowledge about irradiation effects onto the main components of brain ECM such as proteoglycans, glycosaminoglycans, glycoproteins and the enzymes responsible for their modification and degradation.